Combined graph convolutional networks with a multi-connection pattern to identify tremor-dominant Parkinson’s disease and Essential tremor with resting tremor - Zhao, Xiaole; Xiao, Pan; Gui, Honge; Xu, Bintao; Wang, Hongyu; Tao, Li; Chen, Huiyue; Wang, Hansheng; Lv, Fajin; Luo, Tianyou; Cheng, Oumei; Luo, Jing; et al. (Neuroscience, 2024)
•Multi-pattern connection graph convolutional networks can effectively identify essential tremor with resting tremor and tremor-dominant Parkinson’s disease.•Different connection modes may provide distinct discriminative information for diagnosis.•The occipital network and basal ganglion-temporal lobe networks appear to be tremor-related networks for rET and tPD, respectively. Essential tremor with resting tremor (rET) and tremor-dominant Parkinson’s disease (tPD) share many similar clinical symptoms, leading to frequent misdiagnoses. Functional connectivity (FC) matrix analysis derived from resting-state functional MRI (Rs-fMRI) offers a promising approach for early diagnosis and for exploring FC network pathogenesis in rET and tPD. However, methods relying solely on a single connection pattern may overlook the complementary roles of different connectivity patterns, resulting in reduced diagnostic differentiation. Therefore, we propose a multi-pattern connection Graph Convolutional Network (MCGCN) method to integrate information from various connection modes, distinguishing between rET and healthy controls (HC), tPD and HC, and rET and tPD. We constructed FC matrices using three different connectivity modes for each subject and used these as inputs to the MCGCN model for disease classification. The classification performance of the model was evaluated for each connectivity mode. Subsequently, gradient-weighted class activation mapping (Grad-CAM) was used to identify the most discriminative brain regions. The important brain regions identified were primarily distributed within cerebellar-motor and non-motor cortical networks. Compared with single-pattern GCN, our proposed MCGCN model demonstrated superior classification accuracy, underscoring the advantages of integrating multiple connectivity modes. Specifically, the model achieved an average accuracy of 88.0% for distinguishing rET from HC, 88.8% for rET from tPD, and 89.6% for tPD from HC. Our findings indicate that combining graph convolutional networks with multi-connection patterns can not only effectively discriminate between tPD, rET, and HC but also enhance our understanding of the functional network mechanisms underlying rET and tPD.